Penguatan Sumber Daya Manusia melalui Pelatihan Keamanan Pangan dan Standardisasi Produksi pada UMKM Cempedak Goreng Batang Hari, Depok - Anggita Taufiqi; Yuni Pambreni; Tabina Aziz; Syaqila Nur Hidayat; Syahla Izdihar; Shafira Berliyanti; Rizki Saputra Mukti; Nasywa Eka Putri; Najwa Nia Amanda; Dewi Mia Lestari; Adira Aurel; Udriyah Udriyah (Indo Publishing, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in the processed food sector, such as the Cempedak Goreng Batang Hari MSME in Depok, play an important role in the local economy but still face limited knowledge and human resource capacity in implementing food safety principles and proper production standards. This community service activity aims to improve the knowledge and skills of MSME owners in food safety, sanitation hygiene, and production standardization. The implementation method used a participatory counseling and training approach consisting of a preparation stage (observation and preliminary interviews), an implementation stage (face-to-face dialogical material delivery and the handover of a food safety and quality standardization module as a reference for the partner), and an evaluation stage. The results show that the MSME owner experienced improved understanding of sanitation hygiene practices, the use of personal protective equipment, raw material management, and the importance of obtaining a Home Industry Food Production Certificate (SPP-IRT) as a form of legality and product safety assurance. The module provided also serves as a written reference for the partner to carry out a more hygienic and standardized production process sustainably. This activity is expected to be an initial step for the Cempedak Goreng Batang Hari MSME to improve product competitiveness and consumer trust.